A giant primary ovarian fibrosarcoma in a South Sudanese patient - Isaac Rial; Lifteri George Vasilli; Kenneth Sube; Suni Anthony; Stephen Lukudu; Justin Tongun; Joseph Lako (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2024)
Ovarian fibrosarcomas account for less than 1% of all ovarian malignancies. Clinical diagnosis is extremely difficult. A 20-year-old, illiterate, married nulliparous woman presented to our Outpatient Department Clinic (OPD) with chronic abdominal distension. Ultrasound and CT scan revealed a very large intra-abdominal mass, 23.8x27.8x35.7cm. She underwent a laparotomy and left salpingo-oophorectomy with her uterus and right adenexum conserved. After surgery, the mass weighed 11.1kg and measured 43x38x35cm. Histological findings were in line with a giant primary ovarian fibrosarcoma. To date, as far as we are aware, this is the largest ever recorded primary ovarian fibrosarcoma.